Musical agency and the social listener - Palfy, Cora S. (Routledge, 2022)
Music as a narrative drama is an intriguing idea, which has captured explicit music theoretical attention since the nineteenth century. Investigations into narrative characters or personae has evolved into a sub-field--musical agency. In this book, Palfy contends that music has the potential to engage us in social processes and that those processes can be experienced as a social interaction with a musical agent. She explores the overlap between the psychological processes in which we participate in order to understand and engage with people, and those we engage in when we listen to music. Thinking of musical agency as a form of social process is quite different from existing theoretical frameworks for agency. It implies that we come to musical analysis by way of intuition--that our ideas are already partially formed based on our experience of the piece (and what it makes us feel or how it makes us sense it as any other) when we choose to analyze and interpret it. Palfy's focus on social processes is a very effective way to pinpoint when and why it is that our attention is captured and engaged by musical agents.